Digital verification and authentication system for test certificates (DVASTC-COVID-19) - Rassem, Taha H.; Al-Sewari, Abdul Rahman Ahmed Mohammed; Hassan Makbol, Nasrin Mohamed; Waheb Abdul Jabbar, Shaif Abdullah (2021)
Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. The Covid-19 pandemic is a social and an economic crisis just as much as it is a health crisis – its repercussions, severe and far-reaching, are being felt across the world. The COVID-19 negative certificate or test results now becomes very important document for a lot of activities such as air travelling. A lot of cases had been published in the world about fake and change COVID-19 certificates/test results, especially in the airports. The certificates should be provided to permit travelling and immigration. Several approaches may be used to falsify the COVID-19 documents. For example, documents may be copied using copying machines, remade using word processing software or scanned, digitally modified and finally printed.